Emprowering The PKK Team in Pecoro Village, Rambipuji, Jember, Through The Production of Organic Fertilizer From Household Waste. - Supriyadi; Bowo Eko Cahyono; Agus Subekti; Siswanto (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
The empowerment PKK team in Pecoro Village, Rambipui District, Jember Regency has been carried out through organik fertilizer from household waste. The purpose of this activity is to empower PKK women to use household waste into products that can be used. The activity is carried out through lecture / counseling activities, mentoring and the practice of processing organik waste into compost. As a result, the level of awareness of PKK mothers and the community about waste management has increased, and is able to add additional cash and income.